Managing supply chain partnerships - Humphries, Andrew (Henry Stewart Talks, 2010)
Aim is to fill a traditional governance gap in managing strategic supply chain partnerships, Effective enterprise relationship management is a serious challenge of complexity and method, Traditional governance tools and dashboards do not work, A new approach based on a dynamic view of supply chain partnerships is proposed, Two case studies are provided to illustrate tactical and strategic situations, The importance of formal relationship management to the success of supply chain partnerships is emphasised